Frailty Assessment in Advanced Heart Failure - Madan, Shivank A.; Fida, Nadia; Barman, Poulami; Sims, Daniel; Shin, Jooyoung; Verghese, Joe; Piña, Ileana; Jorde, Ulrich; Patel, Snehal R. (Journal of cardiac failure, 2016)
•Prevalence and prognostic value of frailty testing in general heart failure is well established; however, its usefulness in advanced heart failure is unclear.•In our prospective cohort of 40 patients with advanced heart failure, we found that frailty testing is feasible and was predictive of the combined endpoint of all-cause hospitalization and mortality.•On analysis of secondary endpoints, frailty status was also associated with increased all-cause hospitalizations and non-heart failure related hospitalizations.•Frailty assessment in patients with advanced heart failure could provide important prognostic information. [Display omitted] Several studies have recently demonstrated the value of frailty assessment in a general heart failure (HF) population; however, it is unknown whether these findings are also applicable in advanced HF. We investigated the utility of frailty assessment and its prognostic value in elderly patients with advanced HF. Forty consecutive elderly subjects aged ≥65 years, with left ventricular ejection fraction ≤35%, New York Heart Association class III or IV, and a 6-minute walk test <300 m were enrolled from the HF clinic at Montefiore Medical Center between October 2012 and July 2013. Subjects were assessed for frailty with the Fried Frailty Index, consisting of 5 components: hand grip strength, 15-foot walk time, weight loss, physical activity, and exhaustion. All subjects were prospectively followed for death or hospitalization. At baseline, the mean age of the cohort was 74.9 ± 6.5 years, 58% female, left ventricular ejection fraction 25.6 ± 6.4%, 6-minute walk test 195.8 ± 74.3 m and length of follow-up 454 ± 186 days. Thirty-five percent were prefrail and 65% were frail. Frailty status was associated with the combined primary endpoint of mortality and all-cause hospitalization (hazard ratio [HR] 1.93, 95% confidence interval [CI] 1.15–3.25, P = .013). On individual analysis, frailty was associated with all-cause hospitalizations (HR 1.92, 95% CI 1.12–3.27, P = .017) and non-HF hospitalizations (HR 3.31, 95% CI 1.14- 9.6, P = .028), but was not associated with HF hospitalizations alone (HR 1.31, 95% CI 0.68–2.49, P = .380). Frailty assessment in patients with advanced HF is feasible and provides prognostic value. These findings warrant validation in a larger cohort.